Preoperative and perioperative risk factors, and risk score development for prosthetic joint infection due to Staphylococcus aureus: a multinational matched case-control study. (October 2022) - Espindola, Reinaldo; Vella, Venanzio; Benito, Natividad; Mur, Isabel; Tedeschi, Sara; Rossi, Nicolò; Hendriks, Johannes G.E.; Sorlí, Luisa; Murillo, Oscar; Scarborough, Mathew; Scarborough, Claire; Kluytmans, Jan; et al.
Abstract: Objectives: We aim to identify the preoperative and perioperative risk factors associated with post-surgical Staphylococcus aureus prosthetic joint infections (PJI) and to develop and validate risk-scoring systems, to allow a better identification of high-risk patients for more efficient targeted interventions. Methods: We performed a multicenter matched case-control study of patients who underwent a primary hip and knee arthroplasty from 2014 to 2016. Two multivariable models by logistic regression were performed, one for the preoperative and one for perioperative variables; predictive scores also were developed and validated in an external cohort. Results: In total, 130 cases and 386 controls were included. The variables independently associated with S. aureus -PJI in the preoperative period were (adjusted OR; 95% CI): body mass index >30 kg/m 2 (3.0; 1.9 to 4.8), resident in a long-term care facility (2.8; 1.05 to 7.5), fracture as reason for arthroplasty (2.7; 1.4 to 5.03), skin disorders (2.5; 0.9 to 7.04), previous surgery in the index joint (2.4; 1.3 to 4.4), male sex (1.9; 1.2 to 2.9) and American Society of Anesthesiologists index score 3 to 4 (1.8; 1.2 to 2.9). The area under the receiver operating characteristic curve was 0.73 (95% CI 0.68 to 0.78). In perioperative model, the risk factors were the previous ones plus surgical antibiotic prophylaxis administered out of the first 60 minutes before incision (5.9; 2.1 to 16.2), wound drainage for >72 hours after arthroplasty (4.5; 1.9 to 19.4) and use of metal bearing material versus ceramic (1.9; 1.1 to 3.3). The area under the receiver operating characteristic curve was 0.78 (95% CI 0.72 to 0.83). The predictive scores developed were validated in the external cohort. Discussion: Predictive scores for S. aureus -PJI were developed and validated; this information would be useful for implementation of specific preventive measures.